2013
DOI: 10.1002/elps.201200147
|View full text |Cite
|
Sign up to set email alerts
|

Different strategies for the preconcentration and separation of parabens by capillary electrophoresis

Abstract: Several strategies, namely, large volume sample stacking (LVSS), field-amplified sample injection (FASI), sweeping, and in-line SPE-CE, were investigated for the simultaneous separation and preconcentration of a group of parabens. A BGE consisting of 20 mM sodium dihydrogenphosphate (pH 2.28) and 150 mM SDS with 15% ACN was used for the separation and preconcentration of the compounds by sweeping, and a BGE consisting of 30 mM sodium borate (pH 9.5) was used for the separation and preconcentration of the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…In general, these additives can be obtained from nature or manufactured by the chemical industry. The main food additives analyzed by CE in the period covered by this review (2013–2015) were sweeteners , preservatives , and colorants .…”
Section: Food Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, these additives can be obtained from nature or manufactured by the chemical industry. The main food additives analyzed by CE in the period covered by this review (2013–2015) were sweeteners , preservatives , and colorants .…”
Section: Food Additivesmentioning
confidence: 99%
“…Another approach to increase paraben sensitivity is to use on‐column preconcentration strategies prior to CE separation. In this line LVSS, FASI, sweeping, and in‐line SPE‐CE, were investigated for the simultaneous separation and preconcentration of a group of parabens . Methods were optimized for the determination of methylparaben, ethylparaben, propylparaben, isopropylparaben, butylparaben, and benzylparaben and were validated in water samples.…”
Section: Food Additivesmentioning
confidence: 99%
“…B) showed that it was possible to fill the whole volume of the capillary applying a pressure of 1 bar during 1 min. This pressure allows to inject a high sample volume in a shorter time in contrast with other papers in which a higher injection time was applied using lower pressures . The negative voltage (anodic voltage) was checked from −20 to −30 kV.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there are often problems with reproducibility, associated with the process of reproducibly loading and elution . (iii) Packed beds are most commonly used in in‐line SPE‐CE and have been used in many analytical applications . There are different approaches for the construction of a packed bed capillary.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, frits are vulnerable for bubble formation, disrupting the separation. Therefore, fritless packed bed capillaries have been constructed in recent years . In general, the capillary consists of three individual pieces.…”
Section: Introductionmentioning
confidence: 99%